Modelling explicit tides in the Indonesian seas: An important process for surface sea water properties. (June 2018) - Nugroho, Dwiyoga; Koch-Larrouy, Ariane; Gaspar, Philippe; Lyard, Florent; Reffray, Guillaume; Tranchant, Benoit
Abstract: Very intense internal tides take place in Indonesian seas. They dissipate and affect the vertical distribution of temperature and currents, which in turn influence the survival rates and transports of most planktonic organisms at the base of the whole marine ecosystem. This study uses the INDESO physical model to characterize the internal tides spatio-temporal patterns in the Indonesian Seas. The model reproduced internal tide dissipation in agreement with previous fine structure and microstructure observed in-situ in the sites of generation. The model also produced similar water mass transformation as the previous parameterization of Koch-Larrouy et al. (2007 ), and show good agreement with observations. The resulting cooling at the surface is 0.3 °C, with maxima of 0.8 °C at the location of internal tides energy, with stronger cooling in austral winter. The cycle of spring tides and neap tides modulates this impact by 0.1 °C to 0.3 °C. These results suggest that mixing due to internal tides might also upwell nutrients at the surface at a frequency similar to the tidal frequencies. Implications for biogeochemical modelling are important.